Sistem Pemantauan Konsumsi Energi Listrik Rumah Tangga Untuk Validasi Tagihan Listrik Pelanggan - Egi Hergiyan; Muhammad Dzaky; Nadira Desti P.P (Elkom: Jurnal Elektronika dan Komputer, 2026)
Current conventional electrical energy recording systems have limitations in accurately monitoring power consumption fluctuations in real-time. On the other hand, Internet of Things (IoT)-based monitoring solutions are often vulnerable to the risk of data loss during internet connection disruptions on the user's end. This study aims to design a single-phase electrical power consumption monitoring system as a comparison instrument for State Electricity Company (PLN) bills that is robust against network disturbances. The proposed solution is a system based on the ESP32 microcontroller and PZEM-004T sensor, implementing a dual (hybrid) logging method. This system utilizes an SD Card as an independent local storage medium and Google Spreadsheets as a cloud database, which is subsequently visualized through a Grafana dashboard. Processing is managed in parallel using FreeRTOS to prevent program interruptions. Calibration results demonstrate an exceptionally high level of system precision, with a coefficient of determination ($R^2$) of 0.9997 for voltage and 0.9999 for current against standard measuring instruments. Transmission reliability testing over 30 days recorded a 0% data loss rate from a total of 43,200 samples. Furthermore, direct validation against PLN postpaid bills shows a high degree of alignment, where the system's accumulated monthly consumption of 144.541 kWh differed by only 0.541 kWh from the official PLN meter reading (144 kWh). This system is proven effective in preventing data loss while simultaneously functioning as a credible and transparent actual bill comparison instrument for customers.